Corporate Social Responsibility dan Kinerja Perusahaan: Financial Slack sebagai Variabel Moderasi - Anita Anita; Jessica Jessica (Politeknik Ganesha Medan, 2023)
Company performance has become one of the efforts for an entity to survive. During COVID-19 pandemic, the performance of every company in Indonesia experienced a decline in profits, allowing the company's performance to also decline. The purpose of this research is to describe the relationship between corporate social responsibility and financial slack with company performance. With the disclosure of CSR can make a company's performance better and responded well by stakeholders. However, several previous studies reveal that the effect of CSR disclosure on company performance is still less convincing. Therefore, this study also analyzes the role of financial slack as an independent and moderating variable. This research uses quantitative type method. The data used is historical data from the last five years. The object of this research uses data from companies listed on the IDX for 5 years from the 2016-2020 period. Determination of the sample is based on purposive sampling which uses a sample selection method with certain criteria. The results show that CSR disclosure has a significant negative effect on company performance, financial slack as an independent variable has a significant positive effect on company performance and financial slack as a moderating variable weakens the relationship between company performance and CSR disclosure.